2022
DOI: 10.1186/s13006-021-00447-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study on lactation status and breastfeeding challenges in mothers giving birth to preterm infants

Abstract: Background Mothers of preterm infants face many challenges in breastfeeding, especially regarding lactation. This study aimed to investigate the lactation status and challenges in breastfeeding faced by preterm infants’ mothers. Methods We approached 124 mothers who gave birth to preterm infants between 26 May and 31 October 2018 in a tertiary hospital in China. Lactation status and challenges in breastfeeding on day 7 postpartum, at discharge of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
2
18
1
2
Order By: Relevance
“…Some studies also use special categorical indicators derived from the above-mentioned quantitative indicators. It is suggested that cumulative HM-PCT ≥ 50% within 14 days reduces the incidence of NEC in VLBWI by six-fold ( 46 ), while cumulative MOM-PCT ≥ 50% within 14 days was predictive of continued breastfeeding at 3 months corrected gestational age in preterm mothers ( 47 ). Furthermore, HM-DD ≥ 50 ml/kg/day within 28 days reduces the incidence of sepsis in VLBWI while reducing hospitalization costs ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also use special categorical indicators derived from the above-mentioned quantitative indicators. It is suggested that cumulative HM-PCT ≥ 50% within 14 days reduces the incidence of NEC in VLBWI by six-fold ( 46 ), while cumulative MOM-PCT ≥ 50% within 14 days was predictive of continued breastfeeding at 3 months corrected gestational age in preterm mothers ( 47 ). Furthermore, HM-DD ≥ 50 ml/kg/day within 28 days reduces the incidence of sepsis in VLBWI while reducing hospitalization costs ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the present study did not analyze mothers who underwent operative vaginal deliveries and/or delivered prematurely. Those dyads usually need extra support and encounter more difficulties in breastfeeding [ 41 , 42 ]. Said populations, hereby not considered due to the preliminary nature of our study, shall be included in future studies analyzing the impact of the Diary on perceived maternal support and exclusive breastfeeding rates.…”
Section: Discussionmentioning
confidence: 99%
“…For the analyses presented in this article, we calculated the sample size based on the formula n = Z 2 1 − α/2 × pq / d 2 . According to a study conducted in the USA in 2010, the prevalence of DOLII among Cesarean section mothers (estimated p ) was 59.2% [ 6 ]. Based on an allowable deviation of 0.05, statistical power of 90%, and two-tailed significance level of 5%, the minimum required sample size was 300 participants.…”
Section: Methodsmentioning
confidence: 99%
“…We selected the variables from potential confounders of the onset of lactogenesis identified in prior studies from other countries [ 4 , 6 , 20 25 ]. Demographic, medical, and breastfeeding factors for the mother and infant were included in the current analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation